Two-dimensional echocardiography in the diagnosis of ischemic heart disease. Issue 1 (2nd January 2019) - Fagiry, Moram A.; Hassan, Ikhlas A.; Mahmoud, Mustafa Z.
ABSTRACT: Ischemic heart disease (IHD) also known as coronary artery disease (CAD) is one of the major causes of morbidity and mortality. Two-dimensional echocardiography (2D echo) is a non-invasive diagnostic technique that provides information regarding the cardiac function and hemodynamics. This paper was designed to update the reader on the fundamental principles and current applications of 2D echo imaging recommended in patients with known or suspected IHD. Also the recent advances on the prognostic and diagnostic value and the future directions of 2D echo in the evaluation of IHD will be addressed. Although the noninvasive imaging modalities for the evaluation of IHD have expanded over the last decade, 2D echo remains the most cost-effective and risk-effective imaging choice in most settings. The main drawback of echocardiography remains in the limited echogenicity of many patients and its undeniable operator dependence. However, improvement of existing well-established echocardiographic methods (2D echo, stress echocardiography, contrast echocardiography) in conjunction with the development of new emerging echocardiography methods (3D echo, tissue Doppler imaging (TDI), speckle tracking imaging) are anticipated to increase the clinical utility of echocardiography in IHD.